Disordered knowledge of action order in action disorganisation syndrome. - Forde, E; Humphreys, G; Remoundou, M (2004)
We report data on stored knowledge of everyday tasks in a patient, FK, with 'action disorganisation syndrome'. In section 1, we analysed his explicit knowledge of the component actions, and their temporal order. FK showed generally impaired knowledge of everyday tasks relative to controls, and, when knowledge of the temporal order of the actions was probed, he showed particular impairments for the actions making up the final steps in tasks. In section 2 we assessed FK's implicit knowledge of the tasks, by evaluating how knowledge of the tasks influenced his ability to act out sets of instructions. We demonstrate that FK had some implicit knowledge of the tasks, but also, when actions had to be performed in the order as instructed, there was better knowledge of order for actions performed early rather than late in the task. We suggest that disordered task schema contributed to FK's deficits, with impairments on 'end' actions being vulnerable when task order was important for performance.